Pendampingan Pembuatan Akun Media Sosial dan Google Maps sebagai Upaya Digitalisasi UMKM Keripik Chatenori - Putri, Natasya; Ardesta, Pauta Sapa; Saputri, Arnila; Febriansyah, Okta; Hasanah, Uswatun (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The assistance in creating social media accounts and Google Maps is an effort to digitize micro-enterprises, aimingtoenhance marketing and productvis ibility for MSMEs. This activity was conducted in response to the challenges faced by MSME actors, particularly in digital marketing and business licensing. The implementation method in cludes needs identification, training on creating social media accounts (Instagram, TikTok), and setting up business locations on Google Maps. The results of this activity show that the UMKM Kripik Tempe Ibu Susmidaryani successfully utilized digital platforms to expand market reach, improve customer interaction, and build product branding. The conclusion is that digitization through social media and Google Maps can be an effective solution to increase sales and competitiveness of MSMEs in the digital era. Recommendations for the next steps include the need for ongoing training and assistance in managing digital content to ensure the continuous growth of micro-enterprises.